Toy models of developed turbulence - Hnatich, M.; Jurcisin, M.; Repasan, M. (Condensed Matter Physics, 2005)
We have investigated the advection of a passive scalar quantity by incompressible helical turbulent flow within the framework of extended Kraichnan model. Turbulent fluctuations of velocity field are assumed to have the Gaussian statistics with zero mean and defined noise with finite timecorrelation. Actual calculations have been done up to two-loop approximation within the framework of field-theoretic renormalization group approach. It turned out that space parity violation (helicity) of turbulent environment does not affect anomalous scaling which is a peculiar attribute of the corresponding model without helicity. However, stability of asymptotic regimes, where anomalous scaling takes place, strongly depends on the amount of helicity. Moreover, helicity gives rise to the turbulent diffusivity, which has been calculated in one-loop approximation. В рамках узагальненої моделі Крайчана нами досліджено адвекцію пасивної скалярної величини нестисливого спірального турбулентного потоку. Вважалося, що турбулентні флюктуації поля швидкості описуються гаусовою статистикою з нульовим середнім значенням та шумом із скінченими часовими кореляціями. Розрахунки виконано в наближенні двох петель у формалізмі теоретикопольової ренормалізаційної групи. Встановлено, що порушення просторового паритету (спіральність) турбулентного оточення не впливає на аномальний скейлінг, який є специфічною рисою даної моделі без спіральності. Однак стабільність асимптотичних режимів, де має місце аномальний скейлінг, сильно залежить від величини спіральності. Окрім того, спіральність приводить до росту турбулентної дифузії, яка була розрахована в однопетлевому наближенні.